2022
DOI: 10.1088/1361-6463/ac6cb5
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on the mechanism leading to positive synergism in SF6 mixtures with HFO1234ze(E)

Abstract: The electric strength in HFO1234ze(E)/SF6 mixtures is investigated with swarm and breakdown experiments. The density-reduced critical electric field as well as the breakdown voltage measured with both techniques, are found to be higher than that of the pure gases in mixtures with more than 10% SF6. The underlying mechanism for the observed positive synergy is investigated and the explanation proposed by Hunter and Christophorou in [1] is discussed for this mixture. The pressure-dependent attachment rate is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The breakdown results are presented as median with 84.13 and 15.87 percentiles with 75% of confidence according to [21]. The experimental setup is detailed in [1]. Measurements of swarm parameterseffective ionization rate coefficient, bulk drift velocity and density-scaled bulk longitudinal diffusion coefficient-in C 3 H 6 are shown in figure 1 from 10 to 270 Td.…”
Section: Experimental Methods: Swarm and Breakdown Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The breakdown results are presented as median with 84.13 and 15.87 percentiles with 75% of confidence according to [21]. The experimental setup is detailed in [1]. Measurements of swarm parameterseffective ionization rate coefficient, bulk drift velocity and density-scaled bulk longitudinal diffusion coefficient-in C 3 H 6 are shown in figure 1 from 10 to 270 Td.…”
Section: Experimental Methods: Swarm and Breakdown Experimentsmentioning
confidence: 99%
“…In HFO1234yf/SF 6 mixtures, similarly to C 3 H 6 /SF 6 (and contrarily to HFO1234ze(E)/SF 6 in [1]), there is a mixing ratio range-0% to around 25% HFO1234yf (between 100% and close to 74.5% SF 6 )-in which total ionization is higher or equal to that in SF 6 . However, the increase in total attachment is more significant and over-compensates that of ionization, thus enhancing (E/N) crit (note that the attachment rate is higher than in both SF 6 /HFO1234ze(E) and SF 6 /C 3 H 6 in this range).…”
Section: Attachment and Ionization In Sf 6 Mixtures With Propene And ...mentioning
confidence: 95%
See 1 more Smart Citation
“…Hösl et al found that there exists positive synergistic effect in HFO-1234ze(E)/SF 6 gas mixture. The 90% HFO-1234ze(E)/10% SF 6 has a critical electric field of 360 Td, similar to pure SF 6 [9,15]. Basu et al investigated the as numberdensity reduced AC electric breakdown field strength of HFO-1234ze(E) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the single gas with overall superiority over SF 6 with respect to a unique combination of high‐electric strength, good arc quenching capability, low‐boiling point, high‐heat dissipation, high stability, material compatibility, low toxicity, nonflammability, low GWP, and availability on market, has not been found yet up to date. Recently, a few gases with better properties than SF 6 for one or more of these qualities, including CF 3 I, c‐C 4 F 8 , C 4 F 7 N, C 5 F 10 O, C 6 F 12 O, HFO‐1234ze, etc., were characterized extensively as the replacements for SF 6 [5–7]. However, only the corresponding admixtures with the buffer gases (e.g., air, N 2 , or CO 2 ) have been demonstrated to be the promising eco‐friendly replacements for SF 6 in terms of dielectric strength, GWP, and boiling point with respect to the minimum operating temperature for HV power network applications [8].…”
Section: Introductionmentioning
confidence: 99%